Comparison of decellularized human dermal scaffolds versus bovine collagen/elastin matrices for engineering of soft-tissue flaps - Falkner, Florian; Mayer, Simon A.; Heuer, Miriam; Brune, Jan; Helt, Hannah; Bigdeli, Amir K.; Dimmler, Arno; Heimel, Patrick; Thiele, Wilko; Sleeman, Jonathan P.; Bergmeister, Helga; Schneider, Karl H.; et al. (Plastic and reconstructive surgery, 2024)
Background: - Free flap-based soft-tissue reconstruction comes at the price of donor-site morbidity. The arteriovenous loop (AVL) technique can overcome this issue by allowing for the de novo generation of axially vascularized soft-tissue flaps from vein grafts embedded into different matrices. Application of the AVL technique has been limited by insufficient long-term volume retention and poor tissue stability. The authors investigated the suitability of a novel human dermal scaffold to improve volume retention and tissue stability. - Methods: - AVLs were created in 28 immunocompetent rats and embedded in either decellularized human dermal scaffolds (experimental group, n = 14) (Epiflex) or bovine collagen/elastin matrices (control group, n = 14) (MatriDerm) in subcutaneous polytetrafluoroethylene chambers. The weight and volume of engineered tissues, the extent of angiogenesis, and the proportion of proliferating cells were compared between groups on postoperative days (PODs) 21 and 28 by means of immunohistochemistry and micro-computed tomography. - Results: - On POD 28, both groups displayed homogeneous microvascular networks on histopathology and micro-computed tomography. Mean microvessel counts and surface areas and the percentage of proliferating cells did not differ between the groups. However, the experimental human scaffold group displayed significantly smaller volume loss and significantly less tissue degradation compared with bovine matrix controls (volume retention, 102% ± 5% versus 27% ± 7% on POD 21, and 79% ± 12% versus 12% ± 7% on POD 28, respectively; P < 0.0001). - Conclusion: - Compared with bovine matrices, decellularized human scaffolds allow for superior volume retention and tissue stability of de novo engineered soft-tissue AVL flaps in rats. - Clinical Relevance Statement: - AVLs allow for the de novo generation of vascularized soft-tissue flaps. However, insufficient long-term volume retention is still an issue. The authors’ study shows that decellularized human matrices guarantee superior volume stability of de novo grown soft-tissue flaps in rats.